Usefulness of management accounting information in decision making among SMEs: the moderating role of cloud computing / Ruhanita Maelah, Mohammed Fadhil Farhan Al Lami and Gheyath Ghassan - Maelah, Ruhanita; Al Lami, Mohammed Fadhil Farhan; Ghas, Gheyath (Accounting Research Institute (ARI), 2021)
Small and medium sized enterprises (SMEs) are the biggest contributors to the Malaysian economy with more than a third of total gross domestic product (GDP) delivered by these industries. In a competitive business environment, SMEs need to utilize information and technology in making decisions. This study aimed to see the relationship between management accounting information (MAI), decision-making, and cloud computing among SMEs in Malaysia. A quantitative research design utilizing survey questionnaires were used to collect the data. The survey was conducted on 384 Malaysian small and medium-sized enterprises in various sectors. The study obtained 105 useable responses which were analysed using Smart PLS 3.0 (Partial Least Square). The study found all the dimensions of MAI; namely broad scope, timeliness, aggregation and integration, positively related to decision-making. The findings also indicated that cloud computing moderated the relationship between MAI and decision-making. The results provided evidence for organizations to realize the importance of MAI, and strategize how to relate to information characteristics in decision-making. Moreover, it enhances the understanding of SMEs on the role of cloud computing, in light of competitive business environments. Future studies have the opportunity to expand the scope to include samples from other geograpical areas and enhance data collection through case studies and interviews to understand the issue in-depth.